2011
DOI: 10.1111/j.1708-8208.2010.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β and Interleukin‐6 Expression and Gene Polymorphisms in Subjects with Peri‐Implant Disease

Abstract: There was no correlation between the concentration of IL-1β and IL-6 in the crevicular sulcular fluid present in healthy or diseased osseointegrated implants in comparison with healthy teeth. The studied gene polymorphisms had no influence on peri-implant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 37 publications
(81 reference statements)
5
84
3
1
Order By: Relevance
“…In addition, Melo et al . did not take into consideration the presence of bone loss when defining implants with peri‐implantitis. Healthy implants were generally specified as having no bone loss and no signs of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Melo et al . did not take into consideration the presence of bone loss when defining implants with peri‐implantitis. Healthy implants were generally specified as having no bone loss and no signs of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies did not find a significant difference in the level of IL-1β in the crevicular fluid around healthy teeth and implants17,18. Several studies have reported signi-ficantly higher levels of IL-1β in the crevicular fluid around implants than around healthy teeth11,17,19,20,21.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that single nucleotide polymorphisms (SNP) in the IL-1 gene may hold an increased risk for the development of peri-implantitis, particularly when combined with smoking (Andreiotelli et al 2008;Bormann et al 2010). However, the presence of a specific SNP does not necessarily translate into higher levels of IL-1β in PICF (Lachmann et al 2007;Jansson et al 2005;Melo et al 2012). Although there is good evidence of the involvement of IL-1β as a crucial mediator of the host inflammatory response in peri-implant tissues (Murata et al 2002;Salvi et al 2010;Ataoglu et al 2002), this needs to be complemented with further interventional studies, whereby IL-1β inhibitors are part of the treatment.…”
mentioning
confidence: 99%